Design a New Orthosis and Assessment of Its Effects on Knee Joint Kinetics and Kinematics During Gait - Mostafa Kamali; Keyvan Sharifmoradi; Mohammad Taghi Karimi; Mahshid Mosharaf (Islamic Azad University, Hamedan Branch, 2015)
Objective: The number of people suffering from Osteoarthritis (OA) is increasing. Treatment of OA can be done with or without surgery. The most common treatment is using orthosis. However, most patients with OA prefer not to use orthosis because of downward transition. Therefore, the objective of this study was to design new orthosis and to assess its effects on knee joint kinetics and kinematics during gait. Methods: Ten subjects without any neuromuscular disease participated in this study. New orhosis with the same structure of Scottish rite orthosis was designed. Qualysis system analyses with seven cameras as well as a Kistler force plate were used to measure the kinematics and kinetics variables during the gait with and without orthosis. For statistical analysis independent student-t test was used. The significance level was set at p<0.05. Results: Mean walking speed with and without orthosis was not significantly different (p=0.42). Peak anterior- posterior forces applied on knee in the first half of stance phase and propulsion phase was the same during walking with and without orthosis (p>0.05). There was significant difference between peak medio-lateral forces applied on knee during walking with and without orthosis (p<0.05). Conclusion: The new orthosis decreases the adductor moment on knee joint therefore, it can decrease the forces applied on medial compartment of the knee joint. This orthosis improves walking because it does not let inferior transition. This orthosis can improve femur alignment. It is recommended that physiotherapist prescribe this orthosis in order to decrease pain in patients with OA.